Performance analysis of hybrid microhydro power systems. (1st July 2020) - Poudel, R.C.; Manwell, J.F.; McGowan, J.G.
Highlights: Analysis of microhydro power system using Hybrid2 framework. A stochastic model for downscaling of streamflow from daily to hourly time scale. A simplified empirical model of microhydro system in a non-dimensional form. A small pond integrated with a regulated microhydro power system can reduce the battery storage requirements. A method to relate the performance analysis to the Global Tracking Framework for energy access. Abstract: Microhydro power (MHP) system can be an additional renewable energy technology option at many locations around the world to supplement universal access to modern energy stipulated by the Sustainable Development Goals (SDG). Modern microhydro power systems usually employ unregulated turbines and an electronic load controller, a demand-side power management device. Existing analytical models for such systems are lacking details, especially supply-side control, for performance simulation at hourly or sub-hourly scales. As presented in this paper, this work has developed a stochastic model for downscaling of streamflow and an empirical model of MHP system. These models were integrated within the framework of the Hybrid2 tool to simulate the long-term performance of hybrid MHP systems. Three design configurations are presented for a case study in Nepal. The results show that, along with a small pond that can store water for an hour, a hybrid MHP system with half the size of the battery bank can supply the load to comply with the Tier 3 level of energy access stipulated by the Global Tracking Framework (Sustainable Energy for All). Future use of this model will enable designers and developers of MHP systems to enhance performance and cost-effectiveness of hybrid renewable energy systems.